PENGEMBANGAN INSTRUMEN TES PEMECAHAN MASALAH MATEMATIKA PADA MATERI SPLDV - Rilanni Naketi Ayasa,; Alfi Yunita,; Ratulani Juwita, (JOEL: Journal of Educational and Language Research, 2023)
This research was motivated by the test instrument used by teachers at SMP Negeri 7 Padang. The limitations of the test questions used by the teacher emphasize the mastery of basic skills and there is no application of mathematics in everyday life.This study aims to produce a problem solving test instrument that is valid and reliable. This type of research is research and development (R&D) using the Plomp model. The Plomp model consists of 3 phases, namely Preliminary Research, Prototyping Phase and Assessment Phase. The instruments used were interview guidelines and validity sheets. The test subjects in this study were class VIII students of SMP Negeri 7 Padang with a total of 26 students. Where 3 students as one to one test subjects and 23 students as small group test subjects. The results of this study indicate that the student problem solving test instrument is very valid, namely 88.33%. In the reliability analysis the instrument has a high reliable value of 0.72 and the reliability value is in the range of 0.60 < < 80